2020
DOI: 10.1002/sctm.20-0143
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inflammation and fibrosis using soluble epoxide hydrolase inhibitors enhances cardiac stem cell-based therapy

Abstract: Stem cell replacement offers a great potential for cardiac regenerative therapy. However, one of the critical barriers to stem cell therapy is a significant loss of transplanted stem cells from ischemia and inflammation in the host environment. Here, we tested the hypothesis that inhibition of the soluble epoxide hydrolase (sEH) enzyme using sEH inhibitors (sEHIs) to decrease inflammation and fibrosis in the host myocardium may increase the survival of the transplanted human induced pluripotent stem cell deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
(180 reference statements)
0
11
0
Order By: Relevance
“…While several of the COX and LOX metabolites are proinflammatory and have been studied in detail, underpinned by the translation of inhibitors of these enzymatic pathways demonstrated by aspirin and zileuton in the treatment of inflammatory diseases, the translational manipulation of the CYP450 pathway remains unexplored and underutilized clinically. The CYP450 epoxidized products, the epoxyeicosatrienoic acids (EETs) have been shown to have anti-inflammatory with several cardioprotective effects ( Li et al, 2009 , 2011 ; Liu et al, 2010 ; Qiu et al, 2011 ; Sirish et al, 2013 , 2020 ). EETs function primarily as autocrine and paracrine effectors in the cardiovascular system and kidney ( Roman et al, 2000 ; Schmelzer et al, 2005 ).…”
Section: Upstream Therapeutic Targets For Atrial Fibrillationmentioning
confidence: 99%
“…While several of the COX and LOX metabolites are proinflammatory and have been studied in detail, underpinned by the translation of inhibitors of these enzymatic pathways demonstrated by aspirin and zileuton in the treatment of inflammatory diseases, the translational manipulation of the CYP450 pathway remains unexplored and underutilized clinically. The CYP450 epoxidized products, the epoxyeicosatrienoic acids (EETs) have been shown to have anti-inflammatory with several cardioprotective effects ( Li et al, 2009 , 2011 ; Liu et al, 2010 ; Qiu et al, 2011 ; Sirish et al, 2013 , 2020 ). EETs function primarily as autocrine and paracrine effectors in the cardiovascular system and kidney ( Roman et al, 2000 ; Schmelzer et al, 2005 ).…”
Section: Upstream Therapeutic Targets For Atrial Fibrillationmentioning
confidence: 99%
“…However, DIC not only inhibits the COX-1 and COX-2 enzymes, but also affects other pathways including LOX and CYP450 leading to a decrease in the cardioprotective anti-inflammatory metabolites [44]. We have extensively shown that EETs, the CYP450 metabolites, are anti-inflammatory and cardioprotective in preventing ventricular hypertrophy, electrical remodeling, and cardiac fibrosis and reducing both atrial and ventricular arrhythmia inducibility in cardiac hypertrophy and MI models [19,20,45]. Our results in this study demonstrate a decrease in EETs isomers with DIC treatment (Figure S3A) suggesting a reduction in cardioprotection with DIC treatment.…”
Section: Important Insights Into the Mechanisms Underlying Mitochondrial Dysfunction From Chronic Dic Exposure Using Metabolomic Analysesmentioning
confidence: 99%
“…Furthermore, inhibition of sEH has been used to treat rheumatoid arthritis by reducing nociception and inflammation, [ 67 ] to reduce inflammation and fibrosis in the host myocardium by inhibiting sEH, [ 68 ] and to improve vascular repair in the treatment of Kawasaki disease by inhibiting sEH. [ 69 ] sEH inhibitors have recently been shown to be effective in the treatment of sepsis.…”
Section: Sehi and Resolution Of Inflammationmentioning
confidence: 99%
“…Furthermore, TPPU decreased local proinflammatory cytokine concentrations while increasing the levels of the anti‐inflammatory cytokine interleukin‐10 in TMJ tissue. [ 68 ] TPPU was found to decrease inflammation and fibrosis in another trial, making it a promising adjuvant to cardiac stem cell treatment. [ 69 ] In a recent study, TPPU and EC5026 were found to inhibit neuroinflammation in the central nervous system of a lipopolysaccharide‐induced mouse model.…”
Section: Sehis In Clinical Trialsmentioning
confidence: 99%